Penguatan Pengelolaan Proyek dengan Aplikasi Project Management Dashboard pada PT.Global Comtech Sejahtera Medan - Roni Yunis; Djoni; Suminar Ariwibowo (Universitas Lancang Kuning, 2022)
PT. Global Comtech Sejahtera Medan, a company that specializes in civil, mechanical, and electrical engineering (CME), is a Community Service Program (PkM) partner. The company's issue is that project planning, budgeting, and progress are not documented, making decision-making difficult. As a result of these constraints, the Project Management Dashboard (SIMPRO) program must be used to strengthen project management. Beginning with identifying and analyzing problems, determining requirements, designing applications, developing applications, integrating, testing, and mentoring. SIMPRO was developed with reference to the stages in the Software Development Method that were modified with the goal of making it more flexible and easier to achieve the goals that had been set. SIMPRO can keep track of project operations, RAB planning, payments, project costs, petty cash, project status, and reporting. A online dashboard and a mobile application are both included into the program. Project Control (PC) uses the mobile application to report project status in the field, ensuring that the working relationship between PC and Project Manager (PM) runs smoothly and that managed projects are completed on time